2003
DOI: 10.1016/s0735-1097(03)00588-6
|View full text |Cite
|
Sign up to set email alerts
|

Importance of diastolic fractional flow reserve and dobutamine challenge in physiologic assessment of myocardial bridging

Abstract: Physiologic assessment of MB should include dobutamine challenge. Because the overshooting of systolic pressure interferes with and is a cause of error in FFR measurements based on mean pressures, diastolic FFR appears to be the technique of choice for MB assessment, whereas mean FFR should be used with caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
134
1
10

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(154 citation statements)
references
References 32 publications
9
134
1
10
Order By: Relevance
“…This suggests that cardiologists should consider the possibility of coronary spasm in patients with chest pain and MB on coronary angiograms. Several methods have been used to assess MB-related myocardial ischemia due to mechanical compression of the coronary artery by MB, such as pharmacological stress echocardiography [26] , stress myocardial perfusion imaging [27] , intracoronary blood flow velocity measurements [21,26] , and intracoronary pressure measurements [1,21,26,28] . In the current case, we assessed intracoronary pressure using a pressure wire because this technique has a reliable cutoff value [29] and can be used conveniently in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that cardiologists should consider the possibility of coronary spasm in patients with chest pain and MB on coronary angiograms. Several methods have been used to assess MB-related myocardial ischemia due to mechanical compression of the coronary artery by MB, such as pharmacological stress echocardiography [26] , stress myocardial perfusion imaging [27] , intracoronary blood flow velocity measurements [21,26] , and intracoronary pressure measurements [1,21,26,28] . In the current case, we assessed intracoronary pressure using a pressure wire because this technique has a reliable cutoff value [29] and can be used conveniently in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…the MB segment is present even at baseline [21] , only during pharmacological stress [1,26,28] , only within the MB segment [26] , or both within and beneath MB [1,21,28] . These different results may have been due to differences in the severity and degree of the MB itself as well as differences in the methods used to measure intracoronary pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two techniques are complementary, as the first shows "milking" of a segment of the artery (Videos 2,3) while the latter shows the thickness of the bridge or tunnel. The relevance of such a finding can be defined further by measuring diastolic FFR (18), which can help in deciding whether such a segment needs de-tunnelling at the time of myectomy (Figure 9).…”
Section: Myocardial Bridges and Tunnelsmentioning
confidence: 99%
“…Escaned et al 15 demonstrated that the use of diastolic pressure ratios rather than mean pressure ratios may be more accurate in unmasking the physiologic significance of myocardial bridges. In their study, both the mean and diastolic pressure ratios were recorded in 12 symptomatic myocardial bridging patients (9/12 had abnormal non-invasive testing) with and without dobutamine challenge.…”
mentioning
confidence: 99%